Hadoop cluster deployment : construct a modern Hadoop data platform effortlessly and gain insights into how to manage clusters efficiently /: construct a modern Hadoop data platform effortlessly and gain insights into how to manage clusters efficiently. (2013) - Unknown
No abstract available